PEARLS – A multicentre phase II/III trial of extended field radiotherapy for androgen sensitive prostate cancer patients with PSMA‐avid pelvic and/or para-aortic lymph nodes at presentation. (November 2022) - Murray, Julia; Cruickshank, Clare; Bird, Thomas; Bell, Philip; Braun, John; Chuter, Dave; Ferreira, Miguel Reis; Griffin, Clare; Hassan, Shama; Hujairi, Nabil; Melcher, Alan; Miles, Elizabeth; et al.
Highlights: PEARLS investigates a patient group, for which there have been no prospective randomised trials evaluating the effect of radiotherapy. PSMA-PET imaging is used to select patients for different randomisation options. Training and support has been provided before and during the trial to reduce variations of contouring and radiotherapy planning. Abstract: PEARLS is a multi-stage randomised controlled trial for prostate cancer patients with pelvic and/or para-aortic PSMA-avid lymph node disease at presentation. The aim of the trial is to determine whether extending the radiotherapy field to cover the para-aortic lymph nodes (up to L1/L2 vertebral interspace) can improve outcomes for this patient group.